Residential energy efficiency retrofits: potential unintended consequences. Issue 12 (15th October 2019) - Collins, Matthew; Dempsey, Seraphim
Abstract : Improving the energy efficiency of the residential building stock has increasingly been promoted by policy makers as a means of reducing energy demand in the residential sector. We review the literature on some non-energy impacts of energy efficiency retrofitting measures aimed at increasing the air tightness and thermal insulation of residential properties. Specifically, we review the impact of retrofitting measures on indoor pollutants, mould growth, attenuation of radio signal and overheating. We show that without the provision of adequate ventilation, increased air tightness can result in higher levels of indoor pollutants and mould growth. Similarly, we show that in certain circumstances thermal insulation has the potential to result in increased signal attenuation and overheating. We detail the policy implications of these findings and outline policy actions that have been implemented in case study countries where these consequences have been identified as potential issues.